A biographical sketch of Dr. Hernan Miranda-Cueto - Salazar Zuloeta, Jaime Ysrael (2009)
Dr. Hernan Miranda-Cueto was born on April 7th, 1924 in Acobamba province, Huancavelica. He studied medicine in San Fernando medical School, which belongs to San Marcos University. Dr. Miranda was the third Dean of Trujillo University School of Medicine, and he also was appointed as Emeritus Professor. He was a well-recognized researcher and he had a great influence in training many new generations of physicians, not only by teaching medicine, but also by sharing his experience and humanity with his pupils. Dr. Miranda passed away on April 30th, 2009.